EFEKTIVITAS PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KEDISIPLINAN SANTRI DI PONDOK PESANTREN DARUL AMANAH BEDONO - Sabrina Citra Auliya; Raffita Happy Amalia; Ida Khoirun Nikmah (Almustofa Journal of Islamic Studies and Research, 2025)
This study aims to analyze the effectiveness of Islamic religious education in improving the discipline of students (santri) at Darul Amanah Islamic Boarding School (Pondok Pesantren) in Bedono. Employing a qualitative approach, the research collects data through unstructured interviews and participant observation to gain a comprehensive understanding of the educational practices and their impact on student behavior. The study reveals that Islamic religious education at Darul Amanah is highly structured and consistently applied through a range of daily and routine activities, including congregational prayers, classical Islamic book studies such as Kitab Kuning and Amtsilati, Qur'an memorization, night dhikr (mujahadah), and tahlil recitation. Additionally, strict enforcement of rules within the pesantren environment contributes to fostering discipline among the santri.The effectiveness of this educational approach is evidenced by several key mechanisms: habituation through repetitive religious practices, role modeling by teachers and senior students, ongoing educational supervision, and the deep internalization of Islamic moral values. These factors collectively nurture a disciplined lifestyle among the santri, reflected in their orderly behavior, punctuality, adherence to rules, and a growing sense of responsibility in their daily lives. The findings suggest that Islamic religious education in this pesantren context not only imparts religious knowledge but also plays a vital role in character development, particularly in cultivating self-discipline. Overall, this study highlights the integral role of structured Islamic educational activities and moral guidance in shaping disciplined behavior among santri. It provides valuable insights for educators and pesantren administrators seeking to enhance the effectiveness of religious education in fostering discipline and positive character traits among students.